Sovereignty's entailments : first nation state formation in the Yukon - Nadasdy, Paul (University of Toronto Press, 2017)
In recent decades, Indigenous peoples in the Yukon have signed land claim and self-government agreements that spell out the nature of government-to-government relations and grant individual First Nations significant, albeit limited, powers of governance over their peoples, lands, and resources. Those agreements, however, are predicated on the assumption that if First Nations are to qualify as governments at all, they must be fundamentally state-like, and they frame First Nation powers in the culturally contingent idiom of sovereignty. Based on over five years of ethnographic research [carried out] in the southwest Yukon, Sovereignty's Entailments is a close ethnographic analysis of everyday practices of state formation in a society whose members do not take for granted the cultural entailments of sovereignty. This approach enables Nadasdy to illustrate the full scope and magnitude of the "cultural revolution" that is state formation and expose the culturally specific assumptions about space, time, and sociality that lie at the heart of sovereign politics. Nadasdy's timely and insightful work illuminates how the process of state formation is transforming Yukon Indian people's relationships with one another, animals, and the land